PENGARUH KEPERCAYAAN, LOKASI, PELAYANAN, JASA DAN KEAMANAN TERHADAP LOYALITAS NASABAH PADA KOPERASI UNIT DESA ”TANI MULYO” KARANGLANGIT LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
The purpose of this study was to determine the effect of trust, location, services, and security services in KUD "Tani Mulyo" Karanglangit Lamongan. Calculation of SPSS 22.00 for Windows available Multiple linear regression analysis, namely: = 5.895 + 0.190 (X1) + 0.131 (X2) + 0.114 (X3) + 0.143 (X4) + 0.117 (X4). Based on the magnitude of the coefficient of determination (R2) note that the contribution of independent variables are beliefs (X1), the location (X2), services (X3), services (X4), Security (X5) customer loyalty (Y) amounted to 80.1%. based on the results of simultaneous calculations using test F test obtained F count of 22.580, while the significant level α = 0.05 Ftable value of 2.38, so assuming obtained F count> F table with probability (Sig.) of 0.000 <0.05 , it is obtained assuming that Ho is rejected and Ha accepted, jadivariabel smoking has a significant effect on loyalty konsumen.Sedangkan testing on the real rate of 5% partially shows that the confidence variable (X1) indicates tcount> ttable that is equal to 5.716> at 2.021. For variable location (X2) indicates Tcount> ttable 3.450> 2.021. Services for the variable (X3) indicates tcount> ttable that is equal to 3.320> 2.021. For variable services (X4) shows tcount> ttable amounted to 3.339> 2.021. while for the security variable (X5) indicates tcount> ttable amounted to 2.238> 2.021. Based on these effects can be deduced that the variables of trust (X1) has the most dominant influence on customer loyalty (Y) for the greatest obtained t 5.716.